திருக்குறள் கூறும் தொடர்பாடல் : ஓர் அறிநிலை ஆய்வு - Jude Dinesh, K.; Raguram, S. (University of Jaffna, 2017)
Thiruvalluvar taught the concept of life through Thirukkural and it consists of short couplets considered as an identity of cultural richness of Tamils. Thirukkural provided principles that are suitable to all the time periods through three books known as the book of virtue, the book of polity and the book of love. These efforts of Thiruvalluvar made him live in the minds of Tamils forever. The researcher intends to understand the subject matter related to communication expressed in this divine literature. 1330 short couplets compiled into chapters. Thirukkural covered a vast number of subject matters. The objective of this study was to understand the opinions and thoughts expressed in Thirukkural in relation to communication. Building on this objective, the scope of this study only considered the short couplets related to communication. This study includes the facts that the Thirukkural expresses values to life including the way in which communication is supposed to be carried out and also this divine literature explains the ways and methods of communication between us. Even though many books and researches are published in terms of communication, this ancient literature carries very important messages regarding communication. This study employed analysis and descriptive study as research methods. The basis of this study covered the 12 chapters of Thirukkural consisting of matters related to communication. Books, researches and articles related to this subject matter provide secondary information for this study. These secondary sources confirm the fact Thiruvalluvar had a thought process regarding communication and these thoughts were searched and compiled in this study. The study is expected to bring out prophetic and scientific thoughts and reveal valuable guidance in the communication process from ancient divine literature.